(3+3)‐Annulation of Donor–Acceptor Cyclopropanes with Diaziridines. (30th July 2018) - Chagarovskiy, Alexey O.; Vasin, Vladimir S.; Kuznetsov, Vladimir V.; Ivanova, Olga A.; Rybakov, Victor B.; Shumsky, Alexey N.; Makhova, Nina N.; Trushkov, Igor V.
Abstract: The first example of (3+3)‐annulation of two different three‐membered rings is reported herein. Donor‐acceptor cyclopropanes in reaction with diaziridines were found to afford perhydropyridazine derivatives in high yields and diastereoselectivity under mild Lewis acid catalysis. The disclosed reaction is applicable for the broad substrate scope and exhibits an excellent functional group tolerance.